2008
DOI: 10.1152/ajpheart.00168.2008
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic cell core can promote necrotic cell death in cardiomyocytes at physiological extracellular Po2

Abstract: The physical law of diffusion imposes O2 concentration gradients from the plasma membrane to the center of the cell. The present study was undertaken to determine how such intracellular radial gradients of O2 affect the fate of isolated single cardiomyocytes. In single rat cardiomyocytes, mitochondrial respiration was moderately elevated by an oxidative phosphorylation uncoupler to augment the intracellular O2 gradient. At physiological extracellular O2 levels (2-5%), decreases in myoglobin O2 saturation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
3
16
1
Order By: Relevance
“…Since oligomycin blocks the ATPase activity of Complex V, it is protective in these experiments; and because oligomycin protects only against ATP depletion and not depletion of the proton gradient, it is concluded generally that the cytotoxic effect of depletion of the mitochondrial membrane potential is not the loss of the ion gradient per se but the induced loss of ATP (Nieminen et al 1994). Because proton uncouplers stress the capability of the cell to produce ATP, they are synergistic with reagents, such as iodoacetamide, that inhibit ATP production (Takahashi 2008).…”
Section: Carbonyl Cyanide-p-trifluoromethoxyphenylhydrazone (Fccp)mentioning
confidence: 80%
See 1 more Smart Citation
“…Since oligomycin blocks the ATPase activity of Complex V, it is protective in these experiments; and because oligomycin protects only against ATP depletion and not depletion of the proton gradient, it is concluded generally that the cytotoxic effect of depletion of the mitochondrial membrane potential is not the loss of the ion gradient per se but the induced loss of ATP (Nieminen et al 1994). Because proton uncouplers stress the capability of the cell to produce ATP, they are synergistic with reagents, such as iodoacetamide, that inhibit ATP production (Takahashi 2008).…”
Section: Carbonyl Cyanide-p-trifluoromethoxyphenylhydrazone (Fccp)mentioning
confidence: 80%
“…For example, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is highly reactive to iodoacetamide, and this reagent has been used as an inhibitor of glycolysis (Williamson 1967). The essential thiol of creatine kinase is also reactive to alkylation (Table 2), and iodoacetamide will block ATP production from both glucose and creatine phosphate in cardiomyocytes (Takahashi 2008). …”
Section: Iodoacetamidementioning
confidence: 99%
“…It was shown that iodoacetamide perfusion at this concentration selectively and irreversibly inhibits creatine kinase activity without significantly altering the basal ATP level or cardiac function for at least 45 min following completion of the perfusion in the intact heart 8,9,16 . Recent studies have demonstrated that iodoacetamide efficiently inhibits creatine kinase activity in skeletal muscle cells and isolated cardiomyocytes similar to the intact heart model 17,18 . After perfusion, mechanical and intracellular Ca 2+ properties of myocytes (paced at 0.5 Hz) were studied in the contractile buffer containing low Ca 2+ (1.3 mmol/L) before switching to a high Ca 2+ (3.3 mmol/L) contractile buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic heart disease, stroke and cancer are associated with cellular hypoxia and nutrient/glucose deprivation [1], [2], [3], [4]. The Hypoxia Inducible Factor (HIF) family of transcriptional regulators modulates the survival of cells in response to these stressors [5] [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cells possess multiple compensatory mechanisms to preserve cellular bioenergetics across a wide range of oxygen and glucose concentrations, and hypoxia and/or glucose deprivation only become pathologic when these countermeasures are exhausted [17]. During anoxia or ischemia, conditions that limit mitochondrial ATP production, adaptive mechanisms fail and cells undergo an “adaptation-to-death switch” [2], [18], [19], frequently in advance of true bioenergetic collapse. Interestingly, some cancer cells can escape this switch due to malfunctioning death pathways that contribute to their malignant progression [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%